Tomography systems and sensor applications velocity measurement of gas bubbles flow in vertical water column using ultrasonic sensor - Syed Yahya, Syed Redha; Mohamad, Elmy Johana; Faizan Marwah, Omar Mohd; Nasir, Nur Nadia (UTM Publisher, 2018)
The purpose of this paper is to present an implementation of measurement system using ultrasonic sensor to detect and measure the velocity flow of gas bubbles in vertical water column. The selection of the sensors is important and must be suitable to the application design. Consideration on the natural limitation of ultrasonic wave is also noted as the higher the frequency of the ultrasonic sensor, the better the sensitivity but lower penetration depth. 2-pairs of ultrasonic sensors are installed non-invasively at the periphery of an acrylic pipe. The glue is used as the coupling material to mount these ultrasonic sensors. The paper finds that information about the gas bubbles in liquid flow that obtained from the sensors’ measurements. At the end of this project, the data that obtained able to used in working computed controlling, monitoring in related industrial process